MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION - Latifah Midea Lutfin (Jurnal Edukasi dan Penelitian Matematika, 2020)
Learning mathematics has objectives that must be achieved, one of which is the ability to solve mathematical problems. The low ability of students' mathematical problems is because the learning process is not optimal. Therefore, to overcome this, it takes a learning model that can improve students' mathematical problem management skills, one of which is the Group Investigation type cooperative learning model. The purpose of this is to describe whether the cooperative learning type of Group Investigation can improve the mathematical problem skills of students according to a literature study. The type of research used is a literature study on improving the ability of mathematical problems through cooperative learning model type Group Investigation. The conclusion of this study is to apply the cooperative learning model of the Group Investigation type which has a tendency to be able to improve the mathematical problem abilities of students described in articles relating to indicators in these abilities related to the stages in the cooperative learning model type Group Investigation. Keywords—mathematical problem solving abilities, Cooperative Learning, Group Investigation